Ilegality of investments in international arbitration against Peru - Velasquez Melendez , Raffo (2025)
The illegality of the actions of foreign capital in the field of investment arbitration is a recurring theme in the cases defended by the Peruvian State, for which reason the author deals in detail with the usual practices and arguments in these international defenses. For this purpose, he relies on the review of several CIADI arbitral decisions, where the legality of investments has been analyzed in a decisive manner to reject or declare an arbitration claim inadmissible.